CEP3 levels affect starvation-related growth responses of the primary root - Delay, Christina (J Exp Bot, 2019)
CEPs (C-TERMINALLY ENCODED PEPTIDEs) inhibit Arabidopsis primary root growth by unknown mechanisms. We investigated how CEP3 levels control primary root growth. CEP3 peptide application decreased cell division, S-phase cell number, root meristematic cell number, and meristem zone (MZ) size in a dose- and CEP RECEPTOR1-dependent manner. Grafting showed that CEP3-dependent growth inhibition requires root and shoot CEPR1. CEP3 induced mitotic quiescence in MZ cells significantly faster than that induced by nutrient limitation alone. CEP3 also inhibited the restoration of S-phase to mitotically quiescence cells by nutrient resupply without quantitatively reducing TARGET OF RAPAMYCIN (TOR) kinase activity. In contrast, cep3-1 had an increased meristem size and S-phase cell number under nitrogen (N)-limited conditions, but not under N-sufficient conditions. Furthermore, cep3-1 meristematic cells remained in S-phase longer than wild-type cells during a sustained carbon (C) and N limitation. RNA sequencing showed that CEP3 peptide down-regulated genes involved in S-phase entry, cell wall and ribosome biogenesis, DNA replication, and meristem expansion, and up-regulated genes involved in catabolic processes and proteins and peptides that negatively control meristem expansion and root growth. Many of these genes were reciprocally regulated in cep3-1. The results suggest that raising CEP3 induces starvation-related responses that curtail primary root growth under severe nutrient limitation.